Flow-Volume Parameters in COPD Related to Extended Measurements of Lung Volume, Diffusion, and Resistance - Jarenbäck, Linnea; Ankerst, Jaro; Bjermer, Leif; Tufvesson, Ellen (Pulmonary Medicine, 2013)
Classification of COPD into different GOLD stages is based on forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) but has shown to be of limited value. The aim of the study was to relate spirometry values to more advanced measures of lung function in COPD patients compared to healthy smokers. The lung function of 65 COPD patients and 34 healthy smokers was investigated using flow-volume spirometry, body plethysmography, single breath helium dilution with CO-diffusion, and impulse oscillometry. All lung function parameters, measured by body plethysmography, CO-diffusion, and impulse oscillometry, were increasingly affected through increasing GOLD stage but did not correlate with FEV1 within any GOLD stage. In contrast, they correlated fairly well with FVC%p, FEV1/FVC, and inspiratory capacity. Residual volume (RV) measured by body plethysmography increased through GOLD stages, while RV measured by helium dilution decreased. The difference between these RV provided valuable additional information and correlated with most other lung function parameters measured by body plethysmography and CO-diffusion. Airway resistance measured by body plethysmography and impulse oscillometry correlated within COPD stages. Different lung function parameters are of importance in COPD, and a thorough patient characterization is important to understand the disease.